Relatório de Estágio Profissional "O realizar de um sonho: ser professor de Educação Física" - Ricardo Moura de Oliveira (2019)
The aim of the following report is to complement a professional internship completed 2nd cycle in Physical Education Teaching in Primary and Secondary Education. For an inexperienced teacher, this time period is very crucial and demanding, as it is the first time reality is truly faced. In this presented document represents my experience during the 2018/19 academic year, showing all of my growth, evolution and progress, both at personal and professional levels. The Escola Secundária de Rio Tinto is an institution that opened its doors and happily welcomed me. This journey was followed and supported by Training group, made up of three more student-interns, the cooperating teacher from the school and by the coordinating professor from the university. This report is divided in six chapters: i) introduction; ii) personal reasons as to why I am passionate about sports and my expectations for the internship, therefore the name being "Sports & I"; iii) "Training Space" is in regards to the context in which I was inserted in, as well as the importance of working in a practical community and being involved in the school community, especially through my classes; iv) "Realization of Professional Practice - Being a Teacher" is the fourth chapter that exposes all of the work done in preparation for good teaching. It is also where I disclose all of the difficulties and newfound strategies throughout my process of learning while teaching. Here, my investigation project can be found, along with its explained objective of analyzing the quality of feedbacks provided during the class of Physical Education. Finally, in chapter V is the mentioning of all activities excuted inside and outside classes. In conclusion, I present my "Expectations for the Future."